2018
DOI: 10.1556/084.2018.19.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Results of PACTE group’s experimental research on translation competence acquisition. The acquisition of the instrumental sub-competence

Abstract: During the second decade of the twenty-first century, documentation in electronic format has come to form a normal part of the workplace for all professional translators. The aim of this article is to present the results of the acquisition of the instrumental subcompetence, which is based on the use of electronic resources. These results are part of empirical-experimental research carried out by the PACTE group on Translation Competence Acquisition. In this study, the evolution of the acquisition of this sub-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 11 publications
1
25
0
1
Order By: Relevance
“…The students in 2012 preferred employing online resources and felt that paper-based resources were not sufficient to translate, since their access was more restrictive and time consuming. Kuznik and Olalla Soler (2018) investigated the acquisition of instrumental sub-competence in five groups of students from the first year of the degree in Translation and Interpreting at UAB to their entry into the labour market and observed that the students from all the years preferred to employ online resources. In addition to that, the students formed a homogeneous collective, since a very small variation was recorded in relation to the variety of resources used.…”
Section: The Use Of Information Resources In the Translation Competenmentioning
confidence: 99%
See 3 more Smart Citations
“…The students in 2012 preferred employing online resources and felt that paper-based resources were not sufficient to translate, since their access was more restrictive and time consuming. Kuznik and Olalla Soler (2018) investigated the acquisition of instrumental sub-competence in five groups of students from the first year of the degree in Translation and Interpreting at UAB to their entry into the labour market and observed that the students from all the years preferred to employ online resources. In addition to that, the students formed a homogeneous collective, since a very small variation was recorded in relation to the variety of resources used.…”
Section: The Use Of Information Resources In the Translation Competenmentioning
confidence: 99%
“…This variable is intended to collect data on the use of information resources during the translation of a text to acquire cultural knowledge and solve cultural translation problems. In our study, only data on the use of electronic information resources were collected, since in PACTE's translation competence acquisition experiment (Kuznik and Olalla-Soler, 2018) it was found that students hardly used paper-based resources (a 2 per cent of a total of 3,459 queries were performed using paper-based resources).…”
Section: Variables and Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…For Kuznik & Olalla-Soler (2018), the new generation that has grown hand in hand with rapid access to information and communication technology from a wide range of computing tools and devices seems to be less expert. Electronic and online documentation has also created serious difficulties to this group already familiar with the use of technology resources.…”
Section: Introductionmentioning
confidence: 99%